Building a language community through radio in the age of social media: The case of Raidió na Life. (1st April 2020) - Day, Rosemary; Walsh, John
This paper investigates the motivations of volunteers in participating in broadcasting on a community radio station in the age of social media. The station chosen broadcasts in Irish, a minority language in Ireland, although it is also the state's national and first official language. It was founded to support and develop the community of Irish speakers in an English-speaking environment. Raidió na Life is based in Dublin and broadcasts to a mixed and dispersed population of Irish language speakers. One of the original aims of the station was to build a sense of community and linguistic empowerment for these people. Data generated by interviews and focus groups reveal that volunteers do not seem to share these clear-cut aims, in fact they seem to lack a sense of themselves as language or community activists. However, the performances of their roles as voluntary broadcasters, particularly in their engagement with their audiences on air and online, appear to be having the desired effect of building social, cultural and linguistic networks. The article demonstrates how social, communicative and cultural benefits can accrue through traditional broadcasting and new social media, even where practitioners are unaware of this dimension to their work. The element of fun or enjoyment keeps people volunteering and makes it personally worth their while. This is found to be more important than any sense of language or community activism as a motivation for participation in the station and is actually one of the reasons why Raidió na Life has manged to stay so successfully on air for the past 27 years.